Henry Savage will and Savage family genealogical notes - Savage, Henry, 1730-1803.
Certified transcript of the will (1796) of Henry Savage, of Orange County, N.Y., and genealogical notes (1944) on his family.
In part, typewritten transcript.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Savage family; Wills -- New York (State) -- Orange County